Gli equivalenti russi della perifrasi verbale imminenziale italiana stare per - Francesca Biagini (MediAzioni, 2023)
The aim of this paper is to analyse the expression of imminentiality in Russian by collecting equivalents of the Italian periphrasis stare per using the Italian-Russian parallel corpus of the Russian National Corpus. Firstly, the way in which imminentiality is expressed through verbal aspect is considered, and it is shown that with non-durative telic verbs the present imperfective (such as umiraet) and future perfective forms with an adverb expressing imminentiality (such as skoro umrët) are both frequent and interpreted as quasi-synonimic. Subsequently, constructions are investigated in which imminentiality is semantically coded by means of modal verbs and those of intention, where constructions with sobirat’sja-sobrat’sja are the most frequent in the corpus. Lastly, past perfective forms with an approximative adverb (such as edva ne, čut’ ne), or with the particle bylo expressing the so called “past with no present relevance” or “discontinuous past” are taken into account and conclusions are drawn.